2023
DOI: 10.3390/antiox12061307
|View full text |Cite
|
Sign up to set email alerts
|

3-Bromo-4,5-dihydroxybenzaldehyde Protects Keratinocytes from Particulate Matter 2.5-Induced Damages

Ao-Xuan Zhen,
Mei-Jing Piao,
Kyoung-Ah Kang
et al.

Abstract: Cellular senescence can be activated by several stimuli, including ultraviolet radiation and air pollutants. This study aimed to evaluate the protective effect of marine algae compound 3-bromo-4,5-dihydroxybenzaldehyde (3-BDB) on particulate matter 2.5 (PM2.5)-induced skin cell damage in vitro and in vivo. The human HaCaT keratinocyte was pre-treated with 3-BDB and then with PM2.5. PM2.5-induced reactive oxygen species (ROS) generation, lipid peroxidation, mitochondrial dysfunction, DNA damage, cell cycle arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…These findings suggested that ROS are key factors in the induction of inflammation and aging by PM 2.5 , and a solution in natural products was sought. Previously, various studies have revealed that various natural compounds from marine algae can decrease excessive ROS levels in skin cells (20,21). In addition, agar oligosaccharide, a marine prebiotic, has anti-aging effects via the activation of antioxidant enzymes, such as Cu/Zn SOD and CAT, in Drosophila melanogaster (22).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that ROS are key factors in the induction of inflammation and aging by PM 2.5 , and a solution in natural products was sought. Previously, various studies have revealed that various natural compounds from marine algae can decrease excessive ROS levels in skin cells (20,21). In addition, agar oligosaccharide, a marine prebiotic, has anti-aging effects via the activation of antioxidant enzymes, such as Cu/Zn SOD and CAT, in Drosophila melanogaster (22).…”
Section: Discussionmentioning
confidence: 99%